Unlocking the Power of Process-based Reading Models: Pedagogical Insights for the EFL Classrooms - Khadka, Bishnu Kumar (Far Western Review, 2024)
This article discusses the concept of reading as a process rather than a final outcome, emphasizing its importance in the EFL (English as a Foreign Language) classroom. It explores various process-based reading models, highlighting their pedagogical implications. It argues that understanding reading as a process is crucial for effective teaching and learning in the EFL context. The main objective is to provide a comprehensive analysis of process-based reading models and their implications for pedagogy in EFL classrooms. This article delves into the significance of viewing reading as a dynamic process rather than a mere end result within the realm of English as a Foreign Language (EFL) education. It navigates through various process-based reading models, shedding light on their profound implications for pedagogy. Emphasizing the pivotal role of understanding reading as a multifaceted process, the article endeavours to provide a comprehensive examination of these models and their instructional ramifications. Through an extensive literature review, the article scrutinizes the diverse linguistic processes intrinsic to reading, while revisiting prominent process-based models such as Irwin and Baker’s reading comprehension model, and the Triangle Model of Reading. Each model, it elucidates, offers distinctive insights into the reading process: the Triangle Model underscores the interplay between phonological and semantic pathways.